SILVA, Kleber.; PEREIRA, Lauro. Decolonizing the Internationalization of Higher Education in the Global South: Applying Principles of Critical Applied Linguistics. London: Routledge, 2023. - Flannery, Mércia (Cadernos de Linguagem e Sociedade, 2025)
Esta é uma resenha sobre o volume especial do volume especial "Decolonizing the internationalization of higher education in the Global South: applying principles of critical applied linguistics to processes of internationalization", SILVA, K. A.; PEREIRA, L. S. M., London: Routledge, 2023, 286p. ISBN 9781032513447.